Efficacy and safety of rifampicin in patients with persistent hepatocellular secretory failure. Issue 11 (8th August 2021) - Shi, Mingxia; Sheng, Li; Lian, Min; Miao, Qi; Wang, Qixia; Xiao, Xiao; Ma, Xiong
Abstract: Background and Aim: Persistent hepatocellular secretory failure (PHSF) is a rare condition of severe cholestasis caused by drugs, toxins, infection, or temporary biliary obstruction. Real‐world data on rifampicin in cholestasis, particularly among patients with deep jaundice, are scarce. We aimed to expand the knowledge on the efficacy and safety of rifampicin treatment in PHSF patients. Methods: Sixteen patients with PHSF who had received rifampicin treatment (150–300 mg/d) at our institution from September 2016 to July 2020 were included. Treatment efficacy was assessed by 20% improvement in serum total bilirubin (TBIL) concentration at 4 weeks. Follow‐up was continued until the concentration of TBIL returned to normal. Results: Among the 16 enrolled patients, 12 had predisposing factors (drugs, infection, or transient biliary obstruction). ATP8B1 or ABCB11 mutations were detected in the other four patients without trigger events. UGT1A1 mutations were found in 7/10 patients. Before rifampicin treatment, the median TBIL level was 352 μmol/L (range 171–591 μmol/L). TBIL > 20% improvement was observed in 14 patients at 4 weeks. TBIL levels of 14 patients eventually returned to normal after 6–12 weeks of rifampicin treatment. The remaining two patients who did not respond to rifampicin finally recovered after nasobiliary drainage. Except for one patient with transient drug‐induced hepatitis, no other serious adverse events were observed. Conclusions: Rifampicin could be a promising option for most PHSF patients. Most PHSF patients have UGT1A1 deficiency, which may be the target of rifampicin.